The Influence Of Enviromental Support On Children With Special Behavioral Needs In Facin Barriers To Growth And Development At Their Early Age - Suryadi, Yeanny (Sekolah Pascasarjana Universitas Negeri Jakarta, 2024)
This research raises problems related to children with special needs at an early age. It’s mean not only children with special needs in disability cases, but more focus to children special needs in category due to external factors that cause their behavior to be different from the behavior of children in general, among other like prones to tantrum, easy to speak in negativily words to friends even to their teachers, hits for solve their problems, has difficulty getting along and has obstacles in participating in learning activities in kindengarten level classes. This is a qualitative research, with data processing using field observation, interviews, and documents by photos or videos. The results of this research showing that family and environmental treatment of young children give efects to children's behavior in their daily growth and development, especially in the school environment. The conclusion of this research is that apart from the need for counseling at the posyandu and health center level for parents from local goverment, in the future there will be a need for social agencies as early childhood care centers for parents with working professions in certain categories under social service from goverment.